Comparison of fatal traumatic medico-legal cases with postmortem computed tomography and autopsy: A pilot study in Taiwan - Hooi-Nee Ong; I-Hung Chen; Yu-Hsuan Hsieh; Cho-Hsien Hsu; Te-I Weng; Chin-Chen Chang (Journal of the Formosan Medical Association, 2023)
In order to determine the performance of postmortem computed tomography (PMCT) in identifying traumatic-relevant macroscopic findings in medico-legal cases, this retrospective observational pilot study involving nine trauma casualties who had received PMCT prior to autopsy. The comparison of these findings in six anatomical regions as dictated in Injury Severity Score (ISS) were performed. 104 traumatic-relevant findings were identified with achievement of 51% congruent findings. PMCT and autopsy had additionally found 22 and 29 findings respectively. PMCT had highest sensitivity for extremity injury (81.82%), followed by chest (73.91%), head, neck and face (71.43%), and abdomino-pelvic area (50%). It had excellent detection rate in abnormal air collection, fracture, foreign body localization, internal ballistic and intracranial pathology. However, the solid organ and vascular injuries as well as integumentary lesions were the major drawback. In conclusion, incorporation of PMCT to autopsy in medico-legal investigation helps to preserve the most abundant traumatic-relevant injuries compared to either modality.